CHALLENGES AND SOLUTIONS IN IMPLEMENTING THE INDEPENDENT CURRICULUM - Yusroh Jalil (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Challenges and solutions in implementing an independent curriculum at RA AL-WAHDAH. This study aims to find out